Nanoporous and nonporous conjugated donor–acceptor polymer semiconductors for photocatalytic hydrogen production - Sheng, Zhao-Qi; Xing, Yu-Qin; Chen, Yan; Zhang, Guang; Liu, Shi-Yong; Chen, Long (Beilstein Journal of Nanotechnology, 2021)
Conjugated polymers (CPs) as photocatalysts have evoked substantial interest. Their geometries and physical (e.g., chemical and thermal stability and solubility), optical (e.g., light absorption range), and electronic properties (e.g., charge carrier mobility, redox potential, and exciton binding energy) can be easily tuned via structural design. In addition, they are of light weight (i.e., mainly composed of C, N, O, and S). To improve the photocatalytic performance of CPs and better understand the catalytic mechanisms, many strategies with respect to material design have been proposed. These include tuning the bandgap, enlarging the surface area, enabling more efficient separation of electron–hole pairs, and enhancing the charge carrier mobility. In particular, donor–acceptor (D–A) polymers were demonstrated as a promising platform to develop high-performance photocatalysts due to their easily tunable bandgaps, high charge carrier mobility, and efficient intramolecular charge transfer. In this minireview, recent advances of D–A polymers in photocatalytic hydrogen evolution are summarized with a particular focus on modulating the optical and electronic properties of CPs by varying the acceptor units. The challenges and prospects associated with D–A polymer-based photocatalysts are described as well.
Keywords: π-conjugated polymeric photocatalysts; donor–acceptor junctions; nanostructure semiconductors; photocatalytic hydrogen production